Life quality in high school students of Lima city - Grimaldo Muchotrigo, Mirian Pilar (2012)
The purpose of this investigation is to identify and compare the levels of quality of life in studentsThe purpose of this investigation is to identify and compare the levels of quality of life in studentsby sex and socioeconomic status. The sample was composed of 589 students from highschool on the 4th and 5th grade, whose ages ranged between 14 and 18 years. The instrumentused was the Quality of Life Scale of Barnes & Olson. For the analysis of the data were used,means and Anova. We concluded that each group sample of is placed at a level OptimumQuality of Life. The main effects from the sex and socioeconomic level were significant for sex,socio-economic level as well as on the interaction between the two variables.